Sustainable Reduction of Strontium Sulfate Using Bioethanol: A Pathway to Carbon-Neutral SrS Production - Javier E. Morales-Mendoza; Jorge L. Domínguez-Arvizu; Alma B. Jasso-Salcedo; Blanca C. Hernández-Majalca; José L. Bueno-Escobedo; Alejandro López-Ortiz; Virginia H. Collins-Martínez (Reactions)
Achieving net-zero carbon emissions, this study introduces a sustainable pathway for reducing strontium sulfate (SrSO4) and celestite ore to strontium sulfide (SrS) using biofuels (biomethane, bioethanol) derived from agro-industrial waste and green hydrogen. Traditional SrSO4 reduction methods, which rely on fossil-derived reductants like coal and operate at energy-intensive temperatures (1100–1200 °C), generate significant greenhouse gases and toxic byproducts, highlighting the need for eco-friendly alternatives. Experimental results demonstrate that bioethanol outperformed other reductants, achieving 97% conversion of synthetic SrSO4 at 950 °C within 24 min and 74% conversion of natural celestite ore over 6 h. Remarkably, this bioethanol-driven process matches the energy efficiency of the conventional black ash method while enabling carbon neutrality through renewable feedstock utilization, reducing CO2 emissions by 30–50%. By valorizing agro-industrial waste streams, this strategy advances circular economy principles and aligns with Mexico’s national agenda for sustainable industrial practices, including its commitment to decarbonizing heavy industries. This study contributes to sustainable development goals and offers a scalable solution for decarbonizing strontium compound production in the chemical industry.